Government Digital Communication Management in Facing the Health Crisis (Case Study on the Covid-19 Pandemic in Provincial Government) - Erna FEBRIANI; Alo LILIWERI; Mirza RONDA; Catur SURATNOAJI (Indonesia Strategic Sustainability, 2023)
This research is motivated by problems with government communication in the Covid-19 pandemic situation that occurred in Indonesia, in a pandemic situation there was an information overload which resulted in unclear information being received by the provincial government from stakeholders so that the government's digital communication management experienced problems. The purpose of this study is to understand and analyze the digital communication management model that has been implemented by the government in handling information during the Covid-19 Pandemic and find the ideal digital communication management model to deal with the pandemic that occurred at the provincial level. The research methodology uses a post-positivist paradigm with a qualitative research type and a case study approach. The theory used in this study is Karl Weick's organizational information theory and is complemented by the four-step communication management model from Cutlip, Center and Broom. The results of the study found that the government had used a digital communication management model during the Covid-19 pandemic, but its implementation needed to be optimized in digital tools, digital communication competencies and also the organizing information system